(untitled) (Archives of Clinical Psychiatry, 2013)
BACKGROUND: Studies have documented high use of tobacco, alcohol and illicit drugs in patients with panic disorder (PD). The comorbid substance use disorders worsen the prognosis of mood and anxiety disorders. The respiratory subtype (RS) of PD seems to represent a more severe and distinct form of this disorder associated with higher familial history of PD and more comorbidity with other anxiety disorders. OBJECTIVES: Describe the patterns of tobacco, alcohol or illicit drug use in PD patients, and also to ascertain if patients with the RS use these substances more than those of the non-respiratory subtype. METHODS: This is a cross-sectional study with 71 PD patients. The Alcohol Use Disorders Identification Test and Fagerstrom Tobacco Questionnaire were used in the evaluation. Patients with four or five respiratory symptoms were classified in the RS, the remaining patients were classified as non-respiratory subtype. RESULTS: In our sample 31.0% were smokers, 11.3% were hazardous alcohol users and none of them was using illicit drugs. There were no differences between the respiratory and non-respiratory subtypes regarding the use of tobacco, alcohol, cannabis, cocaine, stimulants and hallucinogens. DISCUSSION: The RS was not correlated to the use of tobacco, alcohol and illicit drugs. Additional epidemiological and clinical studies focusing the relationship between PD and substance use are warranted.